IMPLEMENTASI PERATURAN BUPATI NOMOR 84 TAHUN 2018 TENTANG ALOKASI DANA DESA DALAM UPAYA PENINGKATAN KEGIATAN PEMBANGUNAN INFRASTRUKTUR DI KECAMATAN SAMBI KABUPATEN BOYOLALI - Dewi, Dhiyan Kartika (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The village government as the lowest layer of government directly facing the community is required to hold an effective government and plan development well.The obstacle faced by the village government in Sambi sub-district is the role of the community in infrastructure development, the village government is less expert at compiling village documents.The method used in this study is descriptive qualitative by using the theory of policy implementation put forward by Goerge Edward III where variables that determine the effectiveness of implementation are communication, resources, disposition and bureaucratic structure.The implementation of village funds in infrastructure development in Sambi Sub-district, on communication indicators has been good, where the village government held a village development before village funds were implemented to build infrastructure. People give opinions in the musrenbangdes.Indicators of village device resources in the village government need to receive guidance and direction in implementing this village fund.Human resources in the community are adequate because many people already have the title of S-1.Indicators of disposition include commitment, nature of democracy, honesty, attitude of implementors have been very good in implementing village funds according to Perbup No. 84 of 2018 by carrying out development and accountable administratively.Indikaktor Bureaucratic structure in the formation of bureaucratic structure of village fund implementation has not been in accordance with the toxic.